Abfraction lesions reviewed: current concepts - Adriana de Fátima Vasconcelos Pereira; Isis Andréa Venturini Pola Poiate; Edgard Poiate Junior; Walter Gomes Miranda Junior (Faculdade São Leopoldo Mandic, 2008)
Non-carious cervical lesions are characterized by structural loss near the cementoenamel junction, without the presence of caries. Anumber of theories have arisen to explain the etiology of such lesions, although the real causes remain obscure, as is reflected by the contradictory terminology used in the literature. In addition to describing acidic and abrasive processes documented as etiological factors, attention is given to the role of mechanical stress from occlusal load, which is the most accepted theory for the development of abfraction lesions. Considering that tensile stress leads to the failure of restorations in the cervical region and that this is a fruitful area for future research, the present study has highlighted diagnosis, prognosis and the criteria for treatment.